Bamboo Shoot Extract as a Natural Plant Regulator Growth (PGR) Able to Increase Sugarcane Seedling (Saccharum officinarum L.) Growth - Fitria Nugraheni Sukmawati (Gontor AGROTECH Science Journal, 2021)
Sugarcane (Saccharum officinarum L.) is a plant that propagated by vegetative, one of which is the budset system. This propagation is mostly done by farmers, but they have stocks in ordering the roots. One of the efforts to accelerate the formation of these roots can be done by using a Plant Regulator Growth (PGR). PGR from synthetic materials is widely sold in the market, but there are also natural ingredients that can function as PGR, one of which is bamboo shoot extract. This research was to know the effect of bamboo shoot extract concentration as a natural PGR on the growth of sugarcane (Saccharum officinarum L.). The experiments was conducted at the LPP Yogyakarta Polytechnic practical garden, Wedomartani, Sleman, Yogyakarta. This experiment was laid on non factorial Randomized Complete Block Design consisting of 5 treatments which is the concentration of bamboo shoot extract with a ratio of 2:1, 4:1, 6:1, 8:1 (bamboo shoot extract : water), and Control. The results showed that bamboo shoot extract with a concentration of 4:1 is the best treatment. That treatment (4:1) was produce the higher plants, number of leaves, number of tillers, stem diameter, root length, and root wet weight were better than other treatments.